Edukasi Literasi Keuangan dan Kebiasaan Menabung pada Siswa SMA Negeri 2 Tabanan - Ni Wayan Nanik Suaryani Taro Putri; Anak Agung Gede Adi Mega Putra; Kadek Gus De Dwi Putra; Ida Ayu Risna Aprillya; Navisa Nailal Husnah; Yosua Christian Hariyanto; Samuel Anugerah Putra (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Financial literacy is a fundamental skill that should be introduced from an early age to develop healthy financial management habits. This community service activity aimed to improve students’ understanding of financial literacy and encourage saving habits through interactive and practical educational activities. The program was conducted at SMA Negeri 2 Tabanan in November 2025 and involved 32 twelfth-grade students. The material was delivered using the 50-30-20 financial allocation method as a practical solution for managing students’ allowances. The results showed that participants gained a better understanding of the importance of distinguishing between needs, wants, and savings, while also demonstrating high enthusiasm during discussions and increased motivation to save consistently. This program is considered effective as a simple and applicable school-based financial literacy education model.